In-situ neutron diffraction during stress relaxation of a single crystal nickel-base superalloy. (1st April 2017) - Collins, David M.; D'Souza, Neil; Panwisawas, Chinnapat
Abstract: The stress relaxation behaviour of a single crystal nickel-base superalloy has been quantified using time-of-flight neutron diffraction analysis for a range of temperatures relevant to casting. A new iterative analysis methodology is described to isolate the lattice strain behaviour of the γ matrix and γ′ precipitate phases from data obtained sufficiently rapidly to help elucidate the microscopic effect of macroscopic stress relaxation. The independent response of γ and γ′ is revealed, showing the temperature sensitivity of lattice strain relaxation. The γ / γ′ response is discussed in the context of thermo-mechanical conditions that may affect the propensity for recrystallisation. Graphical Abstract: